Neonatal arterial thrombosis at birth - Makwana, Bhavi M.; Rabadia, Priyanka J. (International Journal of Contemporary Pediatrics, 2023)
Neonatal thromboembolism occurs with various predisposition and triggers. Early diagnosis of the thrombosis is challenging and essential for therapeutic interventions. We herein report one newborn who presented with transient patient with arterial thrombosis underwent arterial Doppler and received low molecular weight heparin (LMWH) subcutaneously. Newborns suspected having arterial thrombosis may need urgent surgical intervention along with thrombolytic and anticoagulant therapy to prevent organ ischemia and amputation of extremities.